Anti-thymocyte globulin/G-CSF treatment preserves β cell function in patients with established type 1 diabetes - Haller, Michael J.; Gitelman, Stephen E.; Gottlieb, Peter A.; Michels, Aaron W.; Rosenthal, Stephen M.; Shuster, Jonathan J.; Zou, Baiming; Brusko, Todd M.; Hulme, Maigan A.; Wasserfall, Clive H.; Mathews, Clayton E.; Atkinson, Mark A.; et al. (The Journal of clinical investigation, 2015)
Previous efforts to preserve β cell function in individuals with type 1 diabetes (T1D) have focused largely on the use of single immunomodulatory agents administered within 100 days of diagnosis. Based on human and preclinical studies, we hypothesized that a combination of low-dose anti-thymocyte globulin (ATG) and pegylated granulocyte CSF (G-CSF) would preserve β cell function in patients with established T1D (duration of T1D >4 months and <2 years). A randomized, single-blinded, placebo-controlled trial was performed on 25 subjects: 17 subjects received ATG (2.5 mg/kg intravenously) followed by pegylated G-CSF (6 mg subcutaneously every 2 weeks for 6 doses) and 8 subjects received placebo. The primary outcome was the 1-year change in AUC C-peptide following a 2-hour mixed-meal tolerance test (MMTT). At baseline, the age (mean ± SD) was 24.6 ± 10 years; mean BMI was 25.4 ± 5.2 kg/m²; mean A1c was 6.5% ± 1.1%; insulin use was 0.31 ± 0.22 units/kg/d; and length of diagnosis was 1 ± 0.5 years. Combination ATG/G-CSF treatment tended to preserve β cell function in patients with established T1D. The mean difference in MMTT-stimulated AUC C-peptide between treated and placebo subjects was 0.28 nmol/l/min (95% CI 0.001-0.552, P = 0.050). A1c was lower in ATG/G-CSF-treated subjects at the 6-month study visit. ATG/G-CSF therapy was associated with relative preservation of Tregs. Patients with established T1D may benefit from combination immunotherapy approaches to preserve β cell function. Further studies are needed to determine whether such approaches may prevent or delay the onset of the disease. Clinicaltrials.gov NCT01106157. The Leona M. and Harry B. Helmsley Charitable Trust and Sanofi.